1001 Ways to Relax : How to Beat Stress and Find Perfect Calm - George, Mike (London Duncan Baird, 2003)
Provides enough tips and techniques for a whole lifetimes' quota of of pressures, tensions, gripes, disappointments and burdens.
Include Color Illustrations and Index
Keywords: Stress management -- Relaxation -- Stress (Psychology)